The Influence of Internal Conflict on Party Institutionalization: Case Study of the Democratic Party 2010-2015 - Syaid, Allbert Fitri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study was motivated by conflicts that occurred within the Democratic Party and aimed to be able to see the development of the institutionalization of the Democratic Party both before the conflict occurred and after the conflict occurred within the Democratic Party. In this context and background, this research then be carried out. This study aimed to find answers related to how internal conflicts within the Democratic Party can affect the institutionalization of the Democratic Party. In analyzing this research, researchers used conflict theory and party institutionalization theory. This study used a descriptive qualitative research method. In data collection techniques, primary data was obtained through interviews with relevant informants, and secondary data was obtained through studies of various references from books, search of various sites containing research results, documents of political parties. The results of this study indicated that the internal conflict of the Democratic Party was influenced by the power struggle that occurs within the party. The occurrence of this conflict was also based on the dominance of a strong elite in influencing the course of the organization. Thus, the strong personification of figures in the Democratic Party has a negative impact on the institutionalization of the Democratic Party in the organizational aspects of political parties. The occurrence of this conflict was also based on the dominance of a strong elite influencing the course of the organization. Thus, the strong personification of figures in the Democratic Party has a negative impact on the institutionalization of the Democratic Party in the organizational aspects of political parties. The occurrence of this conflict was also based on the dominance of a strong elite influencing the course of the organization. Thus, the strong personification of figures in the Democratic Party has a negative impact on the institutionalization of the Democratic Party in the organizational aspects of political parties.